(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The introduction of radionuclide research methods into clinical practice, along with X-ray methods [3,4,5], allowed the most objective assessment of the functional state of the lymphatic system. For the first time using indirect lymphography in 1950, Walker [5] visualized the lymphatic vessels of rats with a radioactive colloidal solution. The author subcutaneously injected a radioactive colloid into the interdigital spaces of the foot, then determined the concentration of the radioactive colloid in the lymph taken from the femoral lymphatic vessel. When labeled colloidal particles are introduced into subcutaneous tissue, as a result of changes in osmotic pressure, colloidal particles move into lymph nodes in the lymph gums and through lymph vessels. The problem of treatment of vascular, purulent-septic, a number of therapeutic and oncological diseases with medications remains relevant to date. When administered into the body, medications do not always have a sufficiently high effect due to their low concentration in the lymph nodes. Endolymphatic therapy creates a high concentration of drugs in regional lymph nodes [1, 2], where microbes of many diseases and their toxins from the primary focus accumulate and usually spread through them. During treatment, the use of lymphostimulants enhances the effect of lymphotropic drugs.